Multimodal representation of environmental messages in Indonesian eco-murals - Putri Ayu Andini (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Urban eco-murals in Indonesia have emerged as strategic public texts that blend visual, textual, and symbolic resources to communicate urgent environmental messages in accessible and engaging ways. Objective: This study aims to examine how multimodal features, symbolic representations, and environmental ideologies are constructed and communicated through eco-murals in urban public spaces. Method: Using a qualitative multiple-case study design, the research draws on field documentation, archival sources, and digital platforms, analyzed through Multimodal Discourse Analysis, Barthesian Semiotics, and Environmental Discourse Analysis. Results: Findings reveal that eco-murals integrate color, composition, and metaphor to amplify ecological narratives; deploy symbolic motifs—such as hands nurturing trees or animals in distress—to evoke moral responsibility; and embed environmental ideologies that inspire both urgency and hope. Implication: These visual–verbal ensembles function as cultural interventions, transforming public spaces into ecological learning environments, yet their long-term impact depends on audience engagement and contextual reinforcement. Novelty: This study contributes methodologically by combining multimodal, semiotic, and discourse frameworks, and theoretically by positioning eco-murals as active agents of grassroots environmental activism in urban Indonesia.